Ecological and phytocoenotical assessment of populations of rare and endemic species Erysimum croceum M.Pop (ҚазҰУ Хабаршысы. Биология сериясы, 2019)
The article presents the results of ecological and phytocenotic characteristics of the rare, endemic plant E. croceum M.Pop (E. croceum) in the Ili Alatau.The article presents the results of ecological and phytocenotic characteristics and assessment of the present state of four populations of E. croceum M.Pop (E. croceum) endemic and rare plants located on the right and left banks of the Small Almaty Gorge, in the Great Almaty Gorge and in the Issyk Gorge. The highest density of E. croceum species was noted in the population №3 – 8,25±1,2 pcs./m2, the smallest in the nopopulation №1 – 7,3±0,6 pcs./m2. The results of the study showed that E. croceum grows well where soil moisture is an average of 5 to 14, the level of soil pH is from 4,03 to 5,85.As a result of the study of the cenopopulations of E. croceum, it was revealed that they are located within their optimum, there is no special threat of extinction for this species. Nevertheless, that E. croceum is an endemic species, we recommend the following measures: 1) Ili-Alatau National Nature Park should be monitored and monitored continuously for all four E. croceum populations in the Ili Alatau; 2) The Institute of Botany and Phytointroduction should be introduced into its collections in the Botanical Garden of Almaty E. croceum as an endemic, rare and medicinal species.Key words: population, cenopopulation, life forms of plants, ecological types, floristic elements.